(untitled) (European Journal of Pure and Applied Mathematics, 2018)
The general sequence of positive linear operators containing some well-known operators as special cases were introduced in the earlier work by Srivastava and Gupta [9], which reproduce only the constant functions. In the present sequel, we provide a general sequence of operators which preserve not only the constant functions, but also linear functions.